QLOC : quorums with local reconstruction codes - Datta, Anwitaman (2022)
In this paper we study the problem of consistency in distributed storage systems relying on erasure coding for storage efficient fault-tolerance. We propose QLOC - a flexible framework for supporting the storage of warm data, i.e., data which, while not being very frequently in use, nevertheless continues to be accessed for reads or writes regularly. QLOC builds upon (1) a generic family of local reconstruction codes with guarantees in terms of fault-tolerance, efficient recovery from failures and degraded mode operations, and can be instantiated with parameters customized to requirements such as storage overhead and reliability dictated by user needs and operational environments, and (2) quorum-based consistency mechanisms with support for read-modify-write operations without any underlying atomic primitives, providing deployment choices trading-off fault-tolerance, consistency and concurrency requirements. We carry out a theoretical analysis of the code properties, and experimentally benchmark the performance of the consistency enforcement mechanisms, demonstrating the practicality of the proposed approach.